Dynamic meditation in sports dances - V.I. Omelyanenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to elaborate methods for effective training of sport dancers with help of complex integrated person-centered psychological effect on base of dynamic meditation. Material : 20 dancers at age 40-50 years participated in this research. Duration of the research was 3 hours twice a week within a year. Requirement to the experimental group was ability to dig into condition of dynamic meditation. Psychotherapist initiated them into dynamic meditation. Dancing variations were composed with glance to increasing complexity and dancers' primary competence. In the state of the dynamic meditation the dancers of the experimental group concentrated their attention on their moving body parts and physical feeling. Results: Mastering new figures and variations process quickened in the experimental group in comparison with control group. Approximately 2-5 hours of the dynamic meditation were necessary for correction of the mechanical skills. The group consolidation with interrelations and friendship improvement was observed. Family and at-work atmosphere improved. Physical and mental activity increased. Soreness passed off. Psycho emotional stability appeared. Conclusions : the dynamic meditation use in complex with psychological methods in the dancers' experimental group showed its positive influence upon test subjects. The elaborated methods proved pedagogical effect for sports ballroom dances training of seniors category dancers.